2010
DOI: 10.1007/s11205-010-9724-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Leisure Activities: How do Leisure Activities Contribute to Subjective Well-Being?

Abstract: Leisure activities, Subjective well-being, Quality of life, Age, Gender,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
230
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(253 citation statements)
references
References 30 publications
14
230
2
7
Order By: Relevance
“…Meanwhile, the lowest LVD value is in Xinzhou district (31) in urban suburb, and the values in three suburban districts are below the average-Caidian (81), Hannan (63) and Huangpi district (37). Yet, LVD values in two other suburban districts are higher than the average-Dongxihu (107) and Jiangxia (95).…”
Section: Resultsmentioning
confidence: 96%
“…Meanwhile, the lowest LVD value is in Xinzhou district (31) in urban suburb, and the values in three suburban districts are below the average-Caidian (81), Hannan (63) and Huangpi district (37). Yet, LVD values in two other suburban districts are higher than the average-Dongxihu (107) and Jiangxia (95).…”
Section: Resultsmentioning
confidence: 96%
“…Sheldon and Elliot 1999;Hietalahti et al 2016), and leisure activities and consumption may offer a means to this end (Adams et al 2011;Moschis 2012). Brajša-Žganec et al (2011) showed that the associations between leisure activities and emotional well-being (measured by life satisfaction and happiness) were somewhat different between different age groups. Socializing and going out was associated with emotional well-being in persons aged 31-60, but not among the older participants.…”
Section: Moderators Of Leisure Activities and Well-beingmentioning
confidence: 99%
“…Although life-enhancing needs tend to be devalued, they are essential to achieve acceptable quality of life, allowing individuals to build social relationships, experience positive emotions, and acquire additional skills and knowledge [25] .…”
Section: Durations and Types Of Outdoor Activitiesmentioning
confidence: 99%